Novel Modes of Mechanical Ventilation - Al-Hegelan, Mashael; MacIntyre, Neil R. (Seminars in Respiratory and Critical Care Medicine, 2013)
The overarching goal of positive pressure mechanical ventilation is to provide adequate gas exchange support while not causing harm. Indeed, positive pressure mechanical ventilators are only support technologies, not therapeutic technologies. As such they cannot be expected to “cure” disease; they can only “buy time” for other therapies (including the patient's own defenses) to work.Conventional approaches to positive pressure ventilation involve applying ventilatory patterns mimicking normal ones through either masks or artificial airways. This is usually done with modes of support incorporating assist/control breath-triggering mechanisms, gas delivery patterns governed by either a set flow or pressure, and breath cycling based on either a set volume, a set inspiratory time, or a set flow. Often this support includes positive end-expiratory pressure and supplemental oxygen. In recent decades several novel or unconventional approaches to providing mechanical ventilatory support have been introduced. For these to be considered of value, however, it would seem reasonable that they address important clinical challenges and be shown to improve important clinical outcomes (e.g., mortality, duration of ventilation, sedation needs, complications). This article focuses on challenges facing clinicians in providing mechanical ventilatory support and assesses several novel approaches introduced over the last 2 decades in the context of these challenges.
Keywords: positive pressure mechanical ventilation; pressure support; ventilator-induced lung injury; ventilator synchrony